Kewirausahaan Berbasis Kearifan Lokal Sebagai Strategi Model Bisnis Ritel - Ajeng Mira Herdina; Riesta Devi Kumalasari; Priska Arindya Purnama; Meliana Octavia (Jurnal Manajemen dan Kearifan Lokal Indonesia, 2021)
This study aims to find out the implementation of retail business model strategy in form of entrepreneurship activities based on local wisdom, along with the challenges to implement it. The objects of this study is Pelanusa Community; a business community in Malang City that implements a retail business model based on local wisdom. A qualitative approach with data collection techniques through semi-structured in-depth interviews, non-participant observation, and documentation were used. The informants were selected purposively. The results of the study show that creativity and product innovation that accentuates local culture is the strength of Pelanusa Community to produce final product that has value proposition. This strength is supported by training activities that enhance technical and managerial skills. Strict quality control is also an important element to maintain product quality. However, Pelanusa Community faces challenges in terms of production scale to implement the strategy for its retail business model.